Redox Structures of Humic Acids Derived From Different Sediments and Their Effects on Microbial Reduction Reactions - Zhang, Ning; Zhang, Dong-Dong; Ji, Hong-Da; Yu, Xin-Wei; Zhang, Zhi-Chao; Yang, Sheng-Mao; Zhang, Chun-Fang (Frontiers in Microbiology, 2018)
Herein, we investigated the chemical, electrochemical, and spectroscopic characteristics of humic acids (HAs) extracted from sediments of different origin (Ling Qiao river, Xi Xi wetland, Qi Zhen lake, and Hu Zhou pond in Zhejiang province, China), paying particular attention to their role in the enhancement of nitrate and FeOOH reduction. Notably, the highest C/N ratio (16.16), O/C ratio (1.89) and Fe content (11.57 g kg–1 sample) were observed for HAs extracted from Qi Zhen lake sediment. Cyclic voltammetry analyses confirmed that all HAs contained redox-active groups and exhibited redox potentials between –0.36 and –0.28 V vs. the standard hydrogen electrode. All HAs showed similar Fourier transform infrared spectra with variable absorption intensity, the spectra verified the presence of aromatic C=C, C–H, and C=O of quinone ketones group in HAs. Electron spin resonance suggested that quinone moieties within HAs are the redox-active centers. All HAs promoted the microbial reduction of nitrate and amorphous FeOOH by Shewannella oneidensis strain MR-1, achieving high nitrate reduction extents of 79–98.4%, as compared to the biotic and abiotic control values of 29.6 and 0.006%, respectively. The corresponding extents of Fe(II) production equaled 43.25–60.5%, exceeding those of biotic and abiotic controls (28.5 and 0.005%, respectively). In addition to the highest C/N, O/C ratio and Fe content, HA extracted from Qi Zhen lake sediment also exhibited the highest nitrate and FeOOH reduction performances. Although the proportion of organic redox-active carbon is small, the potential electron-mediating ability is not ignorable. HAs are redox active for enhancing microbial reduction of nitrate and amorphous FeOOH regardless of the location or texture of parent sediments, implying their great potential for acting as redox mediator in enhancing multiple microbial reduction, thereby affecting various biogeochemical processes (i.e., iron cycle, nitrogen cycle, etc.) as well as in situ remediation in anaerobic environment.